Sistem Pendukung Keputusan Menentukan Produk Terbaik Menggunakan Metode Simple Additive Weighting Pada CV. Siantar Simalungun Sukse - Evani Sitohang; Dedy Hartama; Agus Perdana Windarto (LPPM STIKOM Tunas Bangsa, 2021)
CV. Siantar Simalungun Sukses is a form of business that sells various kinds of milk to meet the needs of the community, especially for the people of Pematangsiantar. But CV. Siantar Simalungun Sukses is not the only form of business in Pematangsiantar city, but there are still many supermarkets operating in the same field, so that this will lead to business competition between existing forms of business. To face the business competition, there are many ways that can be done by CV. Siantar Simalungun Success to maintain the quality of the milk products sold, including by analyzing the quality of these products, and price competitiveness.